2018
DOI: 10.21037/jgo.2018.08.07
|View full text |Cite
|
Sign up to set email alerts
|

Demographic disparities in delay of definitive chemoradiation for anal squamous cell carcinoma: a nationwide analysis

Abstract: Background: Prolonged time to treatment initiation (TTI) for patients with curable anal cancer may reduce tumor control. This study investigated demographic disparities in TTI for patients receiving definitive chemoradiation (CRT) for anal squamous cell carcinoma (A-SCC). Methods: Adult patients with A-SCC diagnosed from 2004 to 2014 and treated with definitive CRT were identified in the National Cancer Database (NCDB). TTI was defined as days from diagnosis to start of CRT. A negative binomial regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…Timeliness of care is widely recognized as an important health care quality metric . ASCC patients who are Black, publicly insured, or living in areas with lower education have been shown to experience greater treatment initiation delays . In this study, median time from diagnosis to treatment initiation for the entire cohort was 7.9 weeks, with unpartnered and Medicaid patients suffering longer delays.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Timeliness of care is widely recognized as an important health care quality metric . ASCC patients who are Black, publicly insured, or living in areas with lower education have been shown to experience greater treatment initiation delays . In this study, median time from diagnosis to treatment initiation for the entire cohort was 7.9 weeks, with unpartnered and Medicaid patients suffering longer delays.…”
Section: Discussionmentioning
confidence: 64%
“…27 ASCC patients who are Black, publicly insured, or living in areas with lower education have been shown to experience greater treatment initiation delays. 10 In this study, median time from diagnosis to treatment initiation for the entire cohort was 7.9 weeks, with unpartnered and Medicaid patients suffering longer delays. This is consistent with research in other cancers, in which married patients have been found to present to care at earlier stages and to have improved survival.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The authors hypothesized that this racial disparity could be due to an interplay of structural, cultural, and social barriers to healthcare as well as tumor biology. On the contrary, two more recent NCDB studies, one from 2004 to 2013 and one from 2004 to 2014 both did not find evidence of racial disparities in survival on multivariable analysis 22,24 …”
Section: Discussionmentioning
confidence: 96%